Public Service Innovation in Enhancing Government Transparency and Accountability - Leo Simanulang; Agung Pramudya (Program Pascasarjana Universitas Negeri Makassar, 2021)
This study examines the role of public service innovation in enhancing government transparency and accountability in Indonesia. The study is motivated by the increasing demand for transparency and accountability in public governance and the potential of public service innovation to address these challenges. The study aims to identify the facilitators and challenges of public service innovation in enhancing government transparency and accountability in Indonesia. To achieve the research objectives, this study adopted a qualitative research approach, and data were collected through in-depth interviews with public sector officials and document analysis. The collected data were analyzed using thematic analysis. The study found that public service innovation can enhance government transparency and accountability by providing transparent and efficient public services, promoting citizen participation, and promoting data-driven decision-making. However, the implementation of public service innovation faces several challenges, such as limited funding, a lack of technical expertise, and resistance to change. The findings of this study contribute to the existing literature by highlighting the importance of public service innovation in enhancing government transparency and accountability in Indonesia. The study also provides insights into the facilitators and challenges of public service innovation in the context of Indonesia. The study recommends that public sector organizations need to address the challenges identified in this study and leverage the facilitators to successfully implement public service innovation initiatives that enhance government transparency and accountability.